Key questions in cardiac surgery - Moorjani, Narain; Viola, Nicola; Ohri, Sunil K. (Tfm Pub., 2011)
Key Questions in Cardiac Surgery will systematically cover all the main topics involved in the current practice of a cardiac surgeon. It will incorporate current guidelines for practice (such as from the American Heart Association and European Society of Cardiology) and up-to-date information based on current literature.